Alcohol Consumption and Age-related Macular Degeneration: A Systematic Review and Dose–response Meta-analysis. (2nd December 2021) - Zhang, Jingjing; Mitsuhashi, Toshiharu; Matsuo, Toshihiko; Yorifuji, Takashi; Hamada, Jun; Liu, Yangyang
ABSTRACT: Purpose : To perform a systematic review on the association between alcohol consumption and risk of age-related macular degeneration (AMD) using a meta-analytical approach. Method : Systematic literature research was conducted according to the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines. Both categorical and dose–response meta-analysis was performed separately for early and late AMD. A fixed-effect model was used to calculate pooled effect estimates with 95% confidence interval (CI). Result : Seven studies were included in the analysis with 4, 566 and 440 cases of early and late AMD, respectively. Compared to the nondrinkers or occasional drinkers, the pooled effect estimates for early AMD with moderate (1.19, 95% CI [1.03–1.37]) and heavy (1.24, [1.10–1.39]) alcohol consumption, but not light (0.95, [0.90–1.06]) alcohol consumption, were statistically significant. However, the pooled effect estimates for late AMD with light (1.03, [0.79–1.33]), moderate (1.13, [0.83–1.55]), and heavy (0.98, [0.63–1.53]) alcohol consumption were found to be insignificant. A linear dose–response relationship was established ( P < .05) between alcohol consumption and risk of early AMD, and the pooled effect estimate for an increase in alcohol consumption of 10 g/day was 1.14 (1.08–1.21). Conclusion : Moderate and heavy alcohol consumption could increase the risk of early AMD, but not late AMD, with a linear dose–response relationship.